1991
DOI: 10.1007/bf01453690
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium repletion on growth and protein turnover in sodium-depleted rats

Abstract: This study examines the consequences of sodium chloride supplementation to young rats previously made salt deficient by feeding them a sodium-deficient, chloride-replete diet. Salt-deficient rats received the test diet and distilled water for 10 days. As in our previous studies, rats cared for in this manner grew more slowly than rats fed the identical diet but allowed to drink 37 mM sodium chloride. On day 11, half of the salt-depleted animals received 37 mM sodium chloride in their drinking water. Sodium-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Metabolic acidosis is known to impair growth in rats, and is probably related to a negative sodium balance [37]. In our study, a strong positive relationship was observed between blood HCO3 levels during treatment and height SDS at the last observation, indicating a major role of metabolic acidosis in the development of growth failure in FS.…”
Section: Discussionsupporting
confidence: 54%
“…Metabolic acidosis is known to impair growth in rats, and is probably related to a negative sodium balance [37]. In our study, a strong positive relationship was observed between blood HCO3 levels during treatment and height SDS at the last observation, indicating a major role of metabolic acidosis in the development of growth failure in FS.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, there is a large body of experimental evidence that sodium deficiency is harmful to the growth and development of newborn animals. [13][14][15][16][17][18][19][20] We therefore decided to recall the 46 previously studied sodium supplemented and unsupplemented infants, to perform detailed assessments of their physical, neurologi-cal, psychological, and educational status at 10-13 years of age and to correlate their performance with their sodium intake in the neonatal period.…”
mentioning
confidence: 99%
“…A negative sodium balance is a detrimental factor for growth (1)(2)(3)(4) and in immature animals it has been shown to inhibit DNA synthesis (5). The negative effect on growth persists even if the sodium intake is adequately compensated for at a later time in development (6). This implies that sodium is a permissive factor for optimal growth early in development.…”
mentioning
confidence: 99%